THE IMPACT OF ARTIFICIAL INTELLIGENCE ON MODERN SOFTWARE DEVELOPMENT - Anarbayev Sardorbek Odil o'g'li,; Eshonqulov Oybek Shuhrat oʻgʻli,; Bahronov Shahzodjon Vahobjon oʻgʻli, (TADQIQOTLAR, 2025)
Abstract: Artificial intelligence is making radical changes in the development of modern software. Its development is creating new opportunities for programmers, companies and users, helping to make the process of creating software more efficient, fast and high-quality. The influence of artificial intelligence in the field of software is manifested in many directions, and these effects are reflected in improving the quality of  software  products,  reducing  development  deadlines,  as  well  as  creating  new functionality.